2018
DOI: 10.1039/c8sm00905h
|View full text |Cite
|
Sign up to set email alerts
|

Sonocrystallization of conjugated polymers with ultrasound fields

Abstract: Ultrasound acoustic waves are demonstrated to assemble poly-3-hexylthiophene (P3HT) chains into nanofibers after they are fully dissolved in what are commonly considered to be 'good' solvents. In the absence of ultrasound, the polymer remains fully dissolved and does not self-assemble for weeks. UV-vis spectroscopy, ultra-small angle X-ray scattering (USAXS) and small angle neutron scattering (SANS) are used to characterize the induced assembly process and to quantify the fraction of polymer that forms nanofib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 52 publications
3
26
0
Order By: Relevance
“…Ultrasonication was demonstrated to enable the sonocrystallization of dissolved conjugated polymers which subsequently solidified as nanofibers. 152 In a fully dissolved state, the polymer chains were considered to be thermodynamically instable, but located in a local energetic minimum. However, the mechanical energy provided by the ultrasound-induced cavitation events was sufficient to overcome the energetic barrier, resulting in the formation of crystalline nuclei and the growth of larger nanofibers.…”
Section: Anisotropic Polymer Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasonication was demonstrated to enable the sonocrystallization of dissolved conjugated polymers which subsequently solidified as nanofibers. 152 In a fully dissolved state, the polymer chains were considered to be thermodynamically instable, but located in a local energetic minimum. However, the mechanical energy provided by the ultrasound-induced cavitation events was sufficient to overcome the energetic barrier, resulting in the formation of crystalline nuclei and the growth of larger nanofibers.…”
Section: Anisotropic Polymer Nanoparticlesmentioning
confidence: 99%
“…However, the mechanical energy provided by the ultrasound-induced cavitation events was sufficient to overcome the energetic barrier, resulting in the formation of crystalline nuclei and the growth of larger nanofibers. 152 As the intrinsic order in anisotropic particles is considered to be a decisive factor in overcoming the tendency to surface minimization, insight into the internal particle structure and its correlation with the external shape is of major interest to understand and control particle anisotropy.…”
Section: Anisotropic Polymer Nanoparticlesmentioning
confidence: 99%
“…The self-assembly of π-conjugated semiconducting polymers is a topic of substantial interest in the field of organic electronics. , This self-assembly results in the formation of semicrystalline “aggregates” through chain folding and π–π stacking, facilitating charge-carrier transport along both the conjugated backbone and the π–π stacking direction. , Further, it has been shown that the presence of these polymer aggregates in solution can lead to films with enhanced optoelectronic properties, as determined by improved charge-carrier mobilities of thin films comprising the active layer in organic field-effect transistor devices , or improved power conversion efficiencies from bulk heterojunctions used in solar cells. , Methods to induce aggregation in polythiophenes, in particular, poly­(3-hexylthiophene) or P3HT, have included sonication, , UV irradiation, aging over time, , and poor solvent addition. , However, many of these strategies require significant amounts of energy input or involve the addition of hazardous organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Further, it has been shown that the presence of these polymer aggregates in solution can lead to films with enhanced optoelectronic properties, as determined by improved charge-carrier mobilities of thin films comprising the active layer in organic field-effect transistor devices 2,5 or improved power conversion efficiencies from bulk heterojunctions used in solar cells. 6,7 Methods to induce aggregation in polythiophenes, in particular, poly(3-hexylth-iophene) or P3HT, have included sonication, 8,9 UV irradiation, 10 aging over time, 11,12 and poor solvent addition. 13,14 However, many of these strategies require significant amounts of energy input or involve the addition of hazardous organic solvents.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Several processing conditions have been investigated in order to optimize this process and some have been shown to successfully promote nanowire formation such as the above mentioned favorable solvent selection Han (2015); Chang (2004), solution doping Kim (2010), use of ultrasound Xi (2018), use of an appropriate film deposition technique Diao (2014); Katz (2004), and post-treatments such as thermal ; Cui (2003) and solvent annealing Fu (2015); Dickey (2006); Hu (2014). A long-term (> 2 hours) ageing of the P3HT solution to self-assemble nanowires is one of the simplest methods of P3HT nanowire formation.…”
Section: Introductionmentioning
confidence: 99%